2018
DOI: 10.1186/s40066-018-0197-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds, food applications and health benefits of Parkia speciosa (stinky beans): a review

Abstract: The plant community comprises certain underutilized plant species which has proven to be beneficial to human health. Parkia speciosa is considered as one of the highly underutilized plants with multidimensional utility and benefits. The nutritional composition of the seeds is substantial with rich proteins (6.0-27.5%), fats (1.6-13.3%), carbohydrates (68.3-68.7%), minerals (0.5-0.8%) and fibers (1.7-2.0%). Edible part (100 g) contains essential minerals like calcium (108-265.1 mg), magnesium (29 mg), potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 49 publications
0
48
0
1
Order By: Relevance
“…Household food insecurity is a critical issue as it can affect the nutritional status of each individual in the household. Moreover, optimum nutritional status is required for the foundation of healthy human development [1]. In accordance with national data, there has been an escalation of Indonesian people living in poverty rising from 11.07 percent to 14.47 percent [2].…”
Section: Introductionmentioning
confidence: 99%
“…Household food insecurity is a critical issue as it can affect the nutritional status of each individual in the household. Moreover, optimum nutritional status is required for the foundation of healthy human development [1]. In accordance with national data, there has been an escalation of Indonesian people living in poverty rising from 11.07 percent to 14.47 percent [2].…”
Section: Introductionmentioning
confidence: 99%
“…A digital burette (Titrette, Brand Gmbh + Co KG, Wertheim, Germany) was used to determine the titration volume. Finally, the total acidity was calculated (as tartaric acid is the predominant acid in both fruits) using equation (1).…”
Section: Total Acidity (Ta)mentioning
confidence: 99%
“…Fruits are nature's marvelous gift to the human kind as they possess life-prolonging and protecting components. Fruits provide energy, vitamins, minerals, and phytochemicals; their regular consumption improves the physiological functions and reduces the risk of various diseases [1][2][3]. Health-enhancing functional foods such as fruit wines recently increased public interest for the well-being of life.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that vitamins intake [8,9], fiber intake [10], folate intake [11,12], could decrease the development of esophageal cancer. Intakes of bioactive compounds from various plant sources also reduced the risk of cancer [13][14][15][16]. Previous meta-analyses had been published to assess the association between dietary protein intake and many cancers, such as prostate cancer [17], colorectal cancer [18], ovarian cancer [19] etc.…”
Section: Introductionmentioning
confidence: 99%